Method for Reproducible Shipboard Segmented Flow Analysis Ammonium Measurement Using an In-House Reference Material for Quality Control - Rees, Christine; Janssens, Julie; Sherrin, Kendall; Hughes, Peter; Tibben, Stephen; McMahon, Merinda; McDonald, Jack; Camac, Alicia; Schwanger, Cassie; Marouchos, Andreas (Frontiers in Marine Science, 2021)
Ammonium is a fundamental nutrient for phytoplankton growth in seawater and is a key component of the microbial loop. Ammonium measured in parallel with other nutrients is crucial in understanding the small temporal scale changes in oceanographic ecology. Despite the importance of measuring ammonium at sea, owing to its lability, there is no consensus on the best method. The lack of availability of certified reference materials for ammonium in seawater also makes it difficult to assess the accuracy and reproducibility of ammonium measurements. In this study we present a modified segmented flow analysis method using ortho-phthaldialdehyde (OPA) with fluorescence detection to measure ammonium at sea together with four other macro-nutrients (nitrate, nitrite, silicate and phosphate) in near real time. An in-house ammonium quality control (QC) material was produced to improve the accuracy and repeatability of the measurement at sea. The QC was prepared following two different methods and stored in two types of containers. The suitability of the in-house QC’s as a reference material were assessed onboard the RV Investigator in 2018 during two oceanographic voyages, including one on the repeat SR03 CLIVAR transect. This paper describes the production and assessment of the in-house QC for ammonium in seawater, providing groundwork for creating a short-term stable ammonium reference material for sea going voyages. The uncertainty of this method of ammonium measurement was found to be 0.10 µmol/L at ammonium concentration of 1.0 µmol/L. Results show that preparation of the QC inside a laminar flow cabinet and directly into 10 mL polypropylene sample tubes just prior to the commencement of the voyage improved its stability.